(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Loop gastro-Jejunostomy and Roux-en-Y gastro- Jejunostomy, the commonest reconstructions in gastric surgery, are significantly associated with alkaline reflux gastritis and Roux stasis syndrome (RSS) respectively. The Modified Uncut Roux-en-Y (MUREY) technique could be an effective technique in preventing both the conditions. This prospective observational study was designed to evaluate the effectiveness of Modified UREY reconstruction to prevent RSS and Alkaline reflux gastro-esophagitis while avoiding “Staple- line dehiscence”. A total of 47 patients of gastric outlet obstruction, both benign and malignant, undergoing Modified Uncut Roux-en-Y reconstruction with/ without Gastrectomy at BMCH over the span of July 2014 to July 2016, were incorporated in this study. Patients were followed up from the immediate post-operative periods till discharge and postoperatively for 2 months. There was no incidence of bile reflux or bilious vomiting in the follow-up period. There were two (4.3%) incidences of RSS among the 47 patients (P<0.001). Postoperative endoscopy was carried out in 9 patients to assess the integrity of staple line occlusion which revealed normal looking mucosa of upper GIT with an intact staple line occlusion. There was significant decrease in the average Visick score, from 3.5±0.6 (SD) preoperatively to 1.2±0.4(SD) in the post-operative period. Average increase in the body weight at the time of final follow-up was 6.7%±5.1 kg. The Modified “Uncut Roux-En-Y” reconstruction technique is bothfeasible and safe. It is effective in preventing RSS and alkaline reflux gastritis while preventing Staple-line dehiscence and, can be a preferred technique of gastric bypass. J Bangladesh Coll Phys Surg 2018; 36(4): 139-144